PERANCANGAN RUSUNAWA BAGI MASYARAKAT BERPENGHASILAN RENDAH (MBR) DI KOTA PONTIANAK - Cristabella, Silvia; Khaliesh, Hamdil; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Rapid population growth in Pontianak City, driven by urbanization and high birth rates, poses significant challenges in housing provision, particularly for low-income communities (MBR). Land scarcity, soaring land prices, and limited access to decent housing have led to the proliferation of informal and illegal settlements. Addressing these issues requires vertical housing solutions that are land-use efficient and responsive to the humid tropical climate and regional characteristics. This final project presents the designs of a Simple Rental Apartment (Rusunawa) in Pontianak City that integrates spatial efficiency with passive thermal comfort strategies. The design method employs a descriptive-analytical approach by evaluating livability standards, family ergonomic needs, and technical regulations for high-rise buildings. The design results indicate that the application of a single-loaded corridor typology surrounding an inner courtyard is effective in creating an optimal stack effect and cross-ventilation. Housing units, consisting of Type 36 and Type 24, are designed with space flexibility concepts to enhance visual perception within limited areas. This study concludes that climate-responsive massing and adaptive spatial organization are the primary keys to creating healthy, economical, and sustainable vertical housing in Pontianak City.